Narratives of Low Countries History and Culture Reframing the Past - Gilbert, Lesley; Fenoulhet, Jane (Global Dutch, 2016)
This edited collection explores the ways in which our understanding of the past in Dutch history and culture can be rethought to consider not only how it forms part of the present but how it can relate also to the future. Divided into three parts - the uses of myth and history, the past as illumination of cultural context, and historiography in focus - this book seeks to demonstrate the importance of the past by investigating the transmission of culture and its transformations. It reflects on the history of historiography and looks critically at the products of the historiographic process, such as Dutch and Afrikaans literary history